Grounding Architecture: Unnatural Niemeyer - Comas, Carlos Eduardo; Almeida, Marcos (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2022)
Among the many definitions of nature, one is particularly relevant for architecture: the physical world that exists independently of mankind but includes man in its list of creatures. Among the relationships between architecture and this world that mankind inhabites and transforms, two are particularly relevant for understanding the work of Brazilian architect Oscar Niemeyer (1907-2012) and its legacy. One comes from situation, involving pre-existing conditions and the desired outcomes of their transformation. The other feeds on emulation of known forms. In academic terms, one impacts primarily on architectural composition, the definition of the correct anatomy and physiology of buildings, while the other impacts primarily on characterization, the definition of a distinctive physiognomy properly correlated with the building's anatomy and physiology. Niemeyer was educated at ENBA- the Escola Nacional de Belas Artes in Rio, created in1826 after the École des Beaux-Arts in Paris. A close reading of his works belies the widespread association of his work with fusing nature and architecture and reveals a far more complex attitude.
Keywords: Oscar Niemeyer; Modern Architecture; Brazilian Modern Architecture; Nature and Architecture